A review of silver‐dopped graphene oxide nanocomposite: Synthesis and multifunctional applications. Issue 5 (3rd September 2022) - Thinh, Doan Ba; Dat, Nguyen Minh; Tuyen, Nguyen Ngoc Kim; Tai, Le Tan; Hai, Nguyen Duy; Tinh, Ninh Thi; Huong, Le Minh; Do Dat, Tran; Huong, Quach Thi Thanh; Nam, Nguyen Thanh Hoai; Oanh, Doan Thi Yen; Phong, Mai Thanh; et al.
Abstract: In recent years, the applications of nanomaterials are getting more common in commercial products. Amongst them, silver nanoparticles (AgNPs) are the most well‐known nanomaterials for their outstanding antibacterial properties and potential applications in the biomedical field. The agglomeration of AgNPs due to their high surface energy has diminished the actual antibacterial applications of these plasmonic nanoparticles. To tackle this problem, the AgNPs are grafted onto graphene oxide (GO) sheets (Ag/GO) to minimize the agglomeration of AgNPs and enhance the extraordinary antibacterial characteristics of AgNPs thanks to several outstanding features of GO. Ag/GO composite also exhibits other properties such as good optical sensitivity to trace heavy metal ions, adsorption affinity, and catalytic activity for the removal of organic compounds. With all the possibilities, Ag/GO can be considered a multifunctional nanocomposite that can be applied in various fields such as biomedical treatment and environmental remedy. Abstract :